Factors affecting augmented reality adoption in the retail industry - Syed Shah Alam; Samiha Susmit; Chieh-Yu Lin; Mohammad Masukujjaman; Yi-Hui Ho (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Augmented reality (AR) technology is a computer-generated object that allows users to enrich the experience of products virtually with graphics, images, etc. Due to a lack of studies in developing countries like Malaysia, more studies are necessary to understand the pressing factors of diffusing AR technology for the flourishing retail industry. This research aimed to explore the factors affecting the adoption of AR technology in the retail sector through an extension of the technology acceptance model (TAM). The conceptual model was developed based on additional open-innovation-related constructs to the existing TAM constructs. To test the model, data were collected from 233 retail stores in Malaysia using a structured questionnaire survey. The PLS-based structural equation modeling technique was used to analyze the data. The empirical results confirmed that, except for external support and trading partner pressure, other factors, including perceived usefulness, attitude, competitive pressure, customer pressure, perceived cost, and technological knowledge have significant influences on the intention to use AR technology in retail stores. The attitude mediates the relationship between perceived usefulness and behavioral intention and the relationship between self-efficacy and behavioral intention. As operating cost was a critical factor, managers are advised to deliver various packages of after-sales services and free installation charges to curb expenses. This study improved TAM by offering a comprehensive model with cognitive and open innovation factors and provided suggestions for retail stores when they attempt to adopt AR technology to develop an open business model.
Keywords: 650; augmented reality; retail industry; technology acceptancemodel; open innovation; Malaysia